Public investment and re-election prospects in developed countries - Margarita Katsimi; Vassilis Sarantides (Center for Economic Studies and ifo Institute (CESifo), 2011)
A growing literature suggests that office motivated politicians manipulate fiscal policy instruments in order to seek their re-election. This paper investigates the impact of electoral manipulation of the level and composition of fiscal policy on incumbent's re-election prospects. This impact is estimated for a panel of 21 OECD countries over the period 1972- 1999. Our results suggest that increased public investment during the term in office, as well as a shift in expenditures towards public investment can improve re-election prospects. On the contrary, election year manipulation via public investment does not affect re-election prospects. We also find that voters punish politicians who create deficits during elections, while deficits that proceed the election year have similar, although smaller effects on the reelection prospects.
Keywords: D72; E62; 330; political budget cycles; elections; quality of public expenditure; public investment